Three-dimensional analysis of bone site grafting on the upper extremity on computed tomography scans - Villarreal-Villarreal, Gregorio Alejandro; Simental-Mendía, Mario; Arturo Ramírez Mendoza, Diego; Peña-Martínez, Víctor Manuel; Negreros-Osuna, Adrian A; Alberto Acosta-Olivo, Carlos (Journal of orthopaedic surgery (Hong Kong), 2024)
Purpose To perform a quantitative analysis of the amount of cancellous bone in the distal radius and olecranon process by segmentation of computed tomographic scans. As a secondary analysis, the bone density by Hounsfield units was evaluated at the same sites. Methods Computed tomography angiography images of the upper extremity were analyzed using 3-D Slicer™ medical imaging software. Bone volume (cm3) and density (Hounsfield units) from the cancellous bone between the distal radius and the olecranon process were compared by creating an advanced three-dimensional model. The images were analyzed in duplicate, and an intraclass correlation was performed to assess measurement consistency. Results Twenty subjects were included. A total volume of 5.01 ± 1.21 cm3 and 5.81 ± 1.61 cm3 for the distal radius and the olecranon process (p < .0001), respectively, was found. Regarding Hounsfield units, the density of the olecranon process was 303.1 ± 73.26, and the distal radius was 206.5 ± 63.73 (p < .0001). All intraclass correlation coefficients were >0.992. Conclusion These results suggest that the olecranon process has a greater volume and a higher bone mineral density than the distal radius. With these results, the surgeon will have the ability to decide the quantity and quality of bone grafts according to the surgical procedure.